Bringing the benefits of information technology to industrial hygiene records management - Schaper, Louise; Chesson, B. (CCH Australia Ltd, 2005)
The need to maintain adequate control over documentation is gaining increasing significance within industry and organisations. This need has been precipitated by the increasing litigation culture in society and the prolific quantity of information being created. Organisations need to recognise the implications of these phenomena on their operations and devise procedures and strategies to maximise the efficiency of their records management. This article presents an overview of recent initiatives undertaken by the Western Australian operations of a large mining, refining and smelting company to create a fully electronic, text searchable records management database for all industrial hygiene-related documentation. The system creates a new benchmark for maximising the efficiency of records management and has completely revolutionised the way that records are stored, accessed and retrieved. This project’s applicability and value extend to all aspects of industrial hygiene records management, as well as to other areas in organisations — including legal/litigation, environmental, human resources and workers compensation records.